Perlindungan Hukum Bagi Anak Sekolah Dasar dari Tindakan Kekerasan dan Bulyying - Taroreh, Erwin; Adawiah, Rabiatul (Universitas Ekasakti, 2023)
Children are God's creation that we need to work together to protect because of their limitations. One of the forms of protection provided is legal protection for children who experience some form of violence and bullying. The forms of violence that children often receive will have a negative impact on the child's future. The essence of this article aims to find out how necessary it is to provide legal protection for children as victims of violence and bullying and legal protection for children as victims of violence and bullying according to statutory regulations. Legal protection for children is provided so that children's rights remain protected as stated in the laws and regulations governing child protection, namely that they do not suffer any form of violence as stated in Articles 76A to 76B of Law Number 35 of 2014 as well as legal protection. given for justice for children. In this way, the state provides legal protection to all children which has been regulated to be implemented in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims and Law Number 35 of 2014 concerning Child Protection.